Aortic Versus Dual Perfusion for Retrieval of the Liver After Brain Death: A National Registry Analysis. Issue 11 (8th November 2018) - Hameed, Ahmer M.; Pang, Tony; Yoon, Peter; Balderson, Glenda; De Roo, Ronald; Yuen, Lawrence; Lam, Vincent; Laurence, Jerome; Crawford, Michael; D. M. Allen, Richard; Hawthorne, Wayne J.; Pleass, Henry C.
Abstract : There is lack of consensus in the literature regarding the comparative efficacy of in situ aortic‐only compared with dual (aortic and portal venous) perfusion for retrieval and transplantation of the liver. Recipient outcomes from the Australia/New Zealand Liver Transplant Registry (2007‐2016), including patient and graft survival and causes of graft loss, were stratified by perfusion route. Subgroup analyses were conducted for higher‐risk donors. A total of 1382 liver transplantation recipients were analyzed (957 aortic‐only; 425 dual perfusion). There were no significant differences in 5‐year graft and patient survivals between the aortic‐only and dual cohorts (80.1% versus 84.6% and 82.6% versus 87.8%, respectively) or in the odds ratios of primary nonfunction, thrombotic graft loss, or graft loss secondary to biliary complications or acute rejection. When analyzing only higher‐risk donors (n = 369), multivariate graft survival was significantly less in the aortic‐only cohort (hazard ratio, 0.49; 95% confidence interval, 0.26‐0.92). Overall, there was a trend toward improved outcomes when dual perfusion was used, which became significant when considering higher‐risk donors alone. Inferences into the ideal perfusion technique in multiorgan procurement will require further investigation by way of a randomized controlled trial, and outcomes after the transplantation of other organs will also need to be considered.